A TIP Against the COVID-19 Pandemic - Cherif, Reda (IMF Working Papers; Working Paper ;, 2020)
A universal testing and isolation policy is the most viable way to vanquish a pandemic. Its implementation requires: (i) an epidemiological rather than clinical approach to testing, sacrificing accuracy for scalability, convenience and speed; and (ii) state intervention to ramp up production, similar to True Industrial Policy (TIP), on a global level to achieve a scale and speed the market alone would fail to provide. We sketch a strategy to tackle market failures and implement smart testing, especially in densely populated areas. The estimated cost of testing is dwarfed by its return, mitigating the economic fallout of the pandemic.